Usage of reading comprehension to enhance word problem solving skills in mathematics - Supontawanit, Preyanan; Lertlit, Supinda (JEES (Journal of English Educators Society), 2021)
Thailand’s national tests, O-NET, are administered at the 3rd, 6th, and 9th grade levels. Mathematics is one of the tests. Achievement levels in Mathematics are consistently low. Several studies have shown that there is a link between Mathematics achievement and reading comprehension proficiency. Because previous studies were carried out in other jurisdictions, this study aims to correct this situation. Random sampling was used to select the population from a field of 66 grade six students who were enrolled in a special English programme in a private school, Bangkok. 21 students met the sampling criteria. They sat for a pretest and a posttest test in reading comprehension and in word problem-solving skills in mathematics. Treatment was carried out over a period of 8 weeks. Results showed a high positive correlation between reading comprehension skills and achievement in word problem-solving skills in Mathematics. The results can serve as an encouragement to teachers and their supervisors to focus more directly on improving the reading comprehension skills of students as a means to increasing students’ scores on mathematical word-solving tests. HIGHLIGHTS: This study provided the results that these two-skill were positively related and the improvement on reading comprehension skill could induce the development in word problem-solving skills because they both were affected by working memory as an essential key factor. Providing stress-free reading environments and activities could be an interesting option to improve student’s word problem-solving skills in Mathematics. There is a high positive correlation between reading comprehension skills and achievement in word problem solving in Mathematics.